Working mothers of Malaysia: work-family balance of working mothers in Malaysia and the effect of remote work on productivity, satisfaction and wellbeing - Hassan, Razan (2022)
The COVID-19 pandemic brought about a dynamic change where organizations and employees shifted overnight to working remotely, in light of country level lockdowns to curb infections. In Malaysia, females constitute 47% of the population and comprise 55.3% of the labour workforce. Arrangements for childcare, dependent care and home management have typically been shouldered by women. This is backed by the traditional and religious roles society impose on women, and the assumption that she is responsible for all household domestic roles.